Paclitaxel: new uses for an old drug - Zhang D (Drug Design, Development and Therapy, 2014)
Dongshan Zhang,1,2 Ruhao Yang,1 Shixuan Wang,2 Zheng Dong1,2 1Departments of Emergency Medicine and Nephrology, Second Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 2Department of Cellular Biology and Anatomy, Medical College of Georgia, Georgia Regents University and Charlie Norwood VA Medical Center, Augusta, GA, USA Abstract: Paclitaxel (Taxol), one of the most important anticancer drugs, has been used for therapy of different types of cancers. Mechanistically, paclitaxel arrests cell cycle and induces cell death by stabilizing microtubules and interfering with microtubule disassembly in cell division. Recently, it has been found that low-dose paclitaxel seems promising in treating non-cancer diseases, such as skin disorders, renal and hepatic fibrosis, inflammation, axon regeneration, limb salvage, and coronary artery restenosis. Future studies need to understand the mechanisms underlying these effects in order to design therapies with specificity. Keywords: taxol inflammation, fibrosis, coronary artery restenosis, limb salvage, kidney